Promoting Electrocatalytic Reduction of CO2 to C2H4 Production by Inhibiting C2H5OH Desorption from Cu2O/C Composite. Issue 9 (16th December 2021) - Gao, Yugang; Yu, Shiqiang; Zhou, Peng; Ren, Xixi; Wang, Zeyan; Zheng, Zhaoke; Wang, Peng; Cheng, Hefeng; Liu, Yuanyuan; Wei, Wei; Dai, Ying; Huang, Baibiao
Abstract: The electrochemical CO2 reduction reaction (CO2 RR) has great potential in realizing carbon recycling while storing sustainable electricity as hydrocarbon fuels. However, it is still a challenge to enhance the selectivity of the CO2 RR to single multi‐carbon (C2+ ) product, such as C2 H4 . Here, an effective method is proposed to improve C2 H4 selectivity by inhibiting the production of the other competitive C2 products, namely C2 H5 OH, from Cu2 O/C composite. Density functional theory indicates that the heterogeneous structure between Cu2 O and carbon is expected to inhibit C2 H5 OH production and promote CC coupling, which facilitates C2 H4 production. To prove this, a composite electrode containing octahedral Cu2 O nanoparticles (NPs) (o‐Cu2 O) with {111} facets and carbon NPs is constructed, which experimentally inhibits C2 H5 OH production while strongly enhancing C2 H4 selectivity compared with o‐Cu2 O electrode. Furthermore, the surface hydroxylation of carbon can further improve the C2 H4 production of o‐Cu2 O/C electrode, exhibiting a high C2 H4 Faradaic efficiency of 67% and a high C2 H4 current density of 45 mA cm −2 at −1.1 V in a near‐neutral electrolyte. This work provides a new idea to improve C2+ selectivity by controlling products desorption. Abstract : An effective pathway is proposed to strongly improve the selectivity and activity of electrocatalytic reduction of CO2 to C2 H4 by inhibiting desorption of C2 H5 OH from Cu2 O/carbon composite. Moreover, the surface hydroxylation of carbon can strengthen the effect of suppressing C2 H5 OH desorption of the composite and hence further promote C2 H4 production.